Exploring well-being in a First Nation community : a qualitative study / by Lana Ray. - Ray, Lana (2008)
First Nations people hold the worldview that all human and non-human beings are interconnected. This worldview is imperative to the well-being of not only individuals, but to the community and land as well because it promotes certain values. It is these values which foster healthy relationships, and foster wellness. When an individual is connected to other human and non-human beings wellness is enhanced and when there is a disconnection wellness is deteriorated. This research will explore in greater detail, an interconnected worldview as a framework for wellness in an Anishnaabe community and provide a deeper understanding of some of the factors that serve to connect and disconnect the individual. Study area : Ginoogaming First Nation 300 km. northeast of Thunder Bay near Longlac, Northwestern Ontario (on the shore of Long Lake). Traditional languages Ojibway and Oji-Cree are spoken. The community is a member of the Nishnawbe-Aski Nation and is a party of Treaty Nine (James Bay Treaty). Includes commentary on social and economic conditions, culture, tradition & traditional ways and ceremonies, the land and the individual, hunting, fishing, country foods, environment, spirituality, food, feelings of community, social problems like drug abuse, diabetes, health, etc.